2018
DOI: 10.1053/j.gastro.2018.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of Esophageal Pressurization and Bolus Flow Patterns in Patients With Achalasia Esophagus

Abstract: We observed distinct mechanisms of esophageal pressurization and bolus flow patterns in patients with type 2 or type 3 achalasia esophagus compared with control individuals. These findings will increase our understanding of the mechanisms of dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 28 publications
3
30
1
1
Order By: Relevance
“…In type 3 achalasia, the circular and longitudinal muscle contraction lack co-ordination. Luminal crosssectional area is largest in type 1 and smallest in type 3, which is in accordance with the finding that the esophageal wall is thinnest in type 1 and thickest in type 3 achalasia [76]. Finally, prolonged longitudinal muscle contraction is hypothesized to be responsible for the chest pain and heartburn sensation reported in achalasia patients due to the impact of that contraction on esophageal wall blood perfusion [77] while dysphagia may be related to varying bolus flow patterns [76].…”
Section: Achalasiasupporting
confidence: 81%
“…In type 3 achalasia, the circular and longitudinal muscle contraction lack co-ordination. Luminal crosssectional area is largest in type 1 and smallest in type 3, which is in accordance with the finding that the esophageal wall is thinnest in type 1 and thickest in type 3 achalasia [76]. Finally, prolonged longitudinal muscle contraction is hypothesized to be responsible for the chest pain and heartburn sensation reported in achalasia patients due to the impact of that contraction on esophageal wall blood perfusion [77] while dysphagia may be related to varying bolus flow patterns [76].…”
Section: Achalasiasupporting
confidence: 81%
“…Although absent peristalsis is a defining manometric feature of achalasia, we also previously demonstrated that esophageal contractility can be observed in patients with achalasia during evaluation with FLIP panometry . Presence of non‐occluding esophageal contractions in achalasia was also observed using high‐frequency, intra‐luminal ultrasound and these contractions were associated with the pan‐esophageal pressurization of the type II achalasia subtype . Although antegrade contractions can be seen in achalasia, patients with achalasia tend to have a chaotic pattern consisting of sporadic focal contractions and retrograde propagation.…”
Section: Introductionmentioning
confidence: 68%
“…In the absence of structural processes, motility disorders associated with abnormal inhibition involving the LES manifest esophageal outflow obstruction and are defined on the basis of elevated IRP . We used type 3 achalasia as a control group for this pathophysiologic phenotype, where there is abnormal inhibition involving not just the LES but also the smooth muscle esophageal body resulting in simultaneous or premature contractions . We acknowledge that distal esophageal spasm would have been another useful comparison group; however, this disorder is extremely rare, and adequate patient numbers with distal esophageal spasm could not be identified during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…The primary aim of this study was to compare clinical and motility features in jackhammer esophagus with and without EGJ obstruction, using standard HRM as well as provocative testing with MRS. We hypothesized that a common clinical and pathophysiologic thread could exist between jackhammer esophagus and jackhammer esophagus with EGJ obstruction, similar to that seen in type 3 achalasia. A cohort of type 3 achalasia patients was therefore used as a comparison cohort, where abnormal inhibition results in premature or simultaneous contractility and abnormal LES relaxation . A secondary aim was to correlate pathophysiologic mechanisms with presenting symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation